Suraj Mukhi satween jamaat ke liye - Farooqui, Fouzia, Ahsan (Karachi, Oxford university press, 2023)
Suraj Mukhi for Class 7 is an Urdu textbook by Oxford University Press, designed to develop language proficiency through engaging stories, poems, and essays. It emphasizes reading comprehension, grammar, and creative writing while nurturing an appreciation for Urdu literature and cultural heritage. The book supports critical thinking and effective communication skills.